Spy school - Gibbs, Stuart, 1969- (Simon & Schuster Books for Young Readers, 2012)
Twelve-year-old Ben Ripley leaves his public middle school to attend the CIA's highly secretive Espionage Academy, which everyone is told is an elite science school.